PENGARUH KOMPETENSI EMOSIONAL DAN BUDAYA ORGANISASI TERHADAP DISIPLIN KERJA MELALUI KECERDASAN MORAL PEGAWAI DI PENGADILAN TINGGI PALEMBANG - Nazifah, Yasmin; Sakarina, Sari; Putri, Yuni Adinda (JURSIMA, 2025)
Work discipline is a crucial element in building a professional and accountable institution, particularly in the judicial sector. However, problems such as tardiness, rule violations, and low individual responsibility are still prevalent. This study aims to examine the influence of emotional competence and organizational culture on employee work discipline, both directly and indirectly through moral intelligence as a mediating variable at the High Court of Palembang. This research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to 90 permanent employees and analyzed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with the help of SmartPLS. The findings reveal that both emotional competence and organizational culture significantly influence work discipline, either directly or indirectly through moral intelligence. In addition, moral intelligence also has a significant impact on improving employee discipline. These findings highlight the importance of developing human resources that are not only technically competent but also emotionally intelligent, supported by a positive organizational culture and strong moral values to enhance work discipline within judicial institutions.